2022
DOI: 10.1128/jvi.01334-22
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Response Signaling Is Crucial for Effective Chikungunya Virus Replication

Abstract: Being intracellular parasites, viruses require several host cell machineries for effectively replicating their genome, along with virus-encoded enzymes. One of the strategies involves hijacking of the DDR pathways.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Based on our previous reports, where it was established that maximum CHIKV infection occurs at 8 hours post-infection (hpi) time point in the RAW264.7 macrophages, 8 hpi was selected for cell harvesting to carry out all the experiments of viral infection ( 19 , 22 ). E2, an envelope protein of CHIKV, was taken as a marker to assess CHIKV infection in different host systems ( 19 , 40 , 41 , 45 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our previous reports, where it was established that maximum CHIKV infection occurs at 8 hours post-infection (hpi) time point in the RAW264.7 macrophages, 8 hpi was selected for cell harvesting to carry out all the experiments of viral infection ( 19 , 22 ). E2, an envelope protein of CHIKV, was taken as a marker to assess CHIKV infection in different host systems ( 19 , 40 , 41 , 45 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…The RAW264.7 cell line, TLR4KO RAW cell line, BALB/c and C57BL/6 mice-derived peritoneal monocyte-macrophages were infected with CHIKV-IS as reported earlier with minute modifications ( 19 , 22 , 40 , 41 , 45 , 46 ). Briefly, 4.5x10 6 cells were seeded in 90 mm dishes and allowed to grow for 16-18 h. Next, the cells were washed with 1X PBS 2 times and pre-incubated with either TAK-242 or DMSO for 3 h. For TAK-242 treated conditions, the cells were incubated with 0.5 and/or 1 µM concentrations of TAK-242 for 3 h before infection, during infection and post-infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, combining these compounds with specific direct antiviral compounds may lead to synergistic effects with the potential to develop more comprehensive treatment plans that target multiple pathways. Chatterjee et al (2022) recently identified checkpoint kinase proteins Chk1 and Chk2 (also known as CHEK1 and CHEK2), which are commonly known as DNA damage response proteins, as host factors that are involved in CHIKV replication. Similarly, De Caluwé et al (2021) characterised the role of the CD147 protein complex in CHIKV entry into host cells.…”
Section: Antiviral Strategies Targeting the Virus Replication Cyclementioning
confidence: 99%
“…A wide array of host factors, in addition to the non-structural proteins, leads to effective CHIKV infection ( 1 , 2 ). However, there is still much to explore on how cellular proteins contribute to effective CHIKV infection.…”
Section: Lettermentioning
confidence: 99%